Transformation of the Function of Rural Kitchen from the Late XIX to Early XXI Century (on Material from the Lublin Region) - Tymochowicz, Mariola (In the Kitchen. Cultural Sketches on Space, 2019)
The kitchen for 150 years has fundamentally changed. It related both in space and its functions for the household. First part of the text included description of the transformation Lublin kitchen, which primary was only a part of a room, near the stove and since the 1920s became a separate room. The following describes how this room was used and what were and still are its functions for users (culinary, economic, leisure, hygienic, sacral, ritual and integrative). In spite of these changes, the kitchen remained the most conducive place in the home, where most of the tasks indispensable for the proper functioning of the family are realized.